Numerical Study of Airfoil Selection and Analysis of 3D Flow Phenomenon past Finite-Span Wings for Small UAVs - Fauzi Perdana; Sutardi Sutardi (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2020)
Small unmanned aerial vehicle (SUAV) is an unmanned aircraft vehicle (UAV) that flies at an altitude of lower than 1,100 m from the ground, has a maximum gross takeoff weight of 10 kg, and a flight speed of less than 50 m/s. One of the design factors for the small UAV design with a fixed-wing propeller is the airfoil selection. The selection of an airfoil profile using aerodynamic concepts leads to a performance coefficient that determines the selected airfoil’s sustainability and efficiency. The coefficients used are CL, CD, and CM. Numerical studies were carried out using Computational Fluid Dynamics using XFLR5 and ANSYS Fluent 19.1 software to evaluate airfoils in 2D and evaluate the phenomenon of induced drag on the wings in 3D. Airfoil selection was made on five types of airfoils: AH 83-150 Q, E399, E431, E715, and E662. The coefficients of CL, CD, and CM were obtained by varying α. 3D analysis of selected airfoil geometry with finite span. Simulation of steady conditions using Reynolds-Averaged-Navier-Stokes (RANS) in the Spalart-Allmaras turbulent model with variations of α = 0 ◦ , 8◦ , 12◦ , and 16◦ . The post-processor visualized the flow around the wing with pressure contours, velocity pathlines, and tip vortices. The analysis was carried out on the aerodynamic coefficients of CL, CD, CM, and CMr with α variation on the finite span wing. Based on the research, the results showed that the selected airfoil was E431, the aerodynamic performance of the CL, CD, CL/CD, CM, and CMr wings. In addition, information was also obtained regarding a decrease in the pressure difference between the upper surface and lower surface of the wing with an increasing span, 3D streamline, the extent of the contour of the vorticity magnitude, and a streamline on the wingtip on the upper surface and lower surface of the wing.